Global biomethane and carbon dioxide removal potential through anaerobic digestion of waste biomass - Yanlei Feng; Lorenzo Rosa (Environmental Research Letters, 2024)
Anaerobic digestion is a bioenergy technology that can play a vital role in achieving net-zero emissions by converting organic matter into biomethane and biogenic carbon dioxide. By implementing bioenergy with carbon capture and storage (BECCS), carbon dioxide can be separated from biomethane, captured, and permanently stored, thus generating carbon dioxide removal (CDR) to offset hard-to-abate emissions. Here, we quantify the global availability of waste biomass for BECCS and their CDR and biomethane technical potentials. These biomass feedstocks do not create additional impacts on land, water, and biodiversity and can allow a more sustainable development of BECCS while still preserving soil fertility. We find that up to 1.5 Gt CO _2 per year, or 3% of global GHG emissions, are available to be deployed for CDR worldwide. The conversion of waste biomass can generate up to 10 700 TWh of bioenergy per year, equivalent to 10% of global final energy consumption and 27% of global natural gas supply. Our assessment quantifies the climate mitigation potential of waste biomass and its capacity to contribute to negative emissions without relying on extensive biomass plantations.